2005
DOI: 10.4049/jimmunol.174.6.3626
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Factor Has a Suppressive Activity to IgE-Mediated Chemotaxis of Mast Cells

Abstract: Stem cell factor (SCF), which is well known as a cytokine capable of amplifying development and functions of mast cells, is mainly released from fibroblasts in the peripheral tissue. To investigate whether SCF controlled chemotactic migration of mast cells induced by IgE-specific Ag, murine bone marrow-derived cultured mast cells (BMCMC) and human cord blood-derived cultured mast cells (HuCMC) were preincubated with SCF. Although BMCMC and HuCMC sensitized with IgE directly moved toward specific Ag, preincubat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 60 publications
3
20
0
Order By: Relevance
“…The SCF-treated cells also exhibited a dramatic decrease in their ability to migrate to LTB 4 , while their response to SCF was conversely enhanced. A similar observation in MCs was made by Sawada et al (49). They found that preincubation of BMMCs and hCBMCs with SCF for even 1 h completely suppressed IgE-mediated chemotaxis to Ag, while their ability to migrate to nerve growth factor remained essentially unchanged.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The SCF-treated cells also exhibited a dramatic decrease in their ability to migrate to LTB 4 , while their response to SCF was conversely enhanced. A similar observation in MCs was made by Sawada et al (49). They found that preincubation of BMMCs and hCBMCs with SCF for even 1 h completely suppressed IgE-mediated chemotaxis to Ag, while their ability to migrate to nerve growth factor remained essentially unchanged.…”
Section: Discussionsupporting
confidence: 63%
“…It is of interest that IgE-mediated chemotaxis to Ag has been shown to be mediated, in part, by LTB 4 (22). Sawada et al (49) concluded that locally produced SCF may have an inhibitory effect on chemotaxis of MCs, contributing to their accumulation and enhancement of functions at the peripheral site of inflammation. Our observations of decreased LTB 4 -mediated chemotaxis and the effects of SCF on the LTB 4 receptors seem to support this hypothesis and suggest that the progressive decrease observed by Weller et al (23) in BLT1 expression and MC chemotaxis during maturation may have been partly induced by SCF in the culture medium.…”
Section: Discussionmentioning
confidence: 99%
“…We note, however, that the effects of SCF noted here were a consequence of short-term exposure to SCF. Long-term exposure to SCF might downregulate FcRI-mediated chemotaxis (Sawada et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…4D). Sawada et al [25], on the other hand, reported that SCF suppresses chemotactic migration of mast cells towards Ag. Our observation of Ag1SCF-induced F-actin depolymerization may be relevant to these observations.…”
Section: Discussionmentioning
confidence: 99%